2017
DOI: 10.1039/c7an00349h
|View full text |Cite
|
Sign up to set email alerts
|

Using Raman spectroscopy to assess hemoglobin oxygenation in red blood cell concentrate: an objective proxy for morphological index to gauge the quality of stored blood?

Abstract: Blood banking is an essential aspect of modern medical care. When red blood cells (RBCs) are stored, they become damaged by various chemical processes, such as accumulation of their own waste products and oxidative injury, among others. These processes lead to the development of the RBC storage lesion, a complex condition where the severity is reflected through the morphology of the stored cells. It was hypothesized that Raman spectroscopy could be used to monitor certain structural and compositional changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…The difference spectra in Fig. 1 showed that both IDA and SCD presented lower intensity for the peaks at 1227, 1375, and 1406 cm −1 , which can be assigned to oxyhemoglobin [33,45,46]; the IDA presented lower intensity for the peaks at 753, 1567, 1622, and 1644 cm −1 , assigned to the hemoglobin molecule [46][47][48][49][50] and higher intensity for the peak at 1131 cm −1 , assigned to the pyrrolic ring of the porphyrin; the SCD presented lower intensity for the peak at 1004 cm −1 , assigned to aromatic ring of amino acids (phenylalanine) [51], and higher intensity for the peaks at 1215, 1358, 1526, 1547, and 1622 cm −1 , assigned to deoxyhemoglobin [45,46,50]. All of these labeled peaks showed statistically significant differences when comparing the three groups (HbA, IDA, and SCD) (one-way ANOVA test, p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The difference spectra in Fig. 1 showed that both IDA and SCD presented lower intensity for the peaks at 1227, 1375, and 1406 cm −1 , which can be assigned to oxyhemoglobin [33,45,46]; the IDA presented lower intensity for the peaks at 753, 1567, 1622, and 1644 cm −1 , assigned to the hemoglobin molecule [46][47][48][49][50] and higher intensity for the peak at 1131 cm −1 , assigned to the pyrrolic ring of the porphyrin; the SCD presented lower intensity for the peak at 1004 cm −1 , assigned to aromatic ring of amino acids (phenylalanine) [51], and higher intensity for the peaks at 1215, 1358, 1526, 1547, and 1622 cm −1 , assigned to deoxyhemoglobin [45,46,50]. All of these labeled peaks showed statistically significant differences when comparing the three groups (HbA, IDA, and SCD) (one-way ANOVA test, p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
“…The number of spectral features revealed by the loadings suggests specific biochemical changes caused by both types of anemia compared to HbA. The loading vector 1 (Loading 1) presents the spectral features referred to whole blood [28,41,44,46], with positive peaks at 753,1004,1215,1227,1358,1375,1406,1526,1547,1567,1622, and 1644 cm −1 assigned to blood cells (mainly erythrocytes) [28,41] and plasma constituents (mainly albumin) [44]. The Score 1 showed statistically significant differences between the groups IDA versus HbA, SCD versus HbA, and IDA versus SCD (one-way ANOVA, Tukey posttest, p < 0.05), with lower intensity for the IDA and higher intensity for the SCD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So the hemoglobin oxygenation state can be identied by monitoring the ratio (1209 cm À1 /1222 cm À1 ) of the deoxyHb/oxyHb bands which corresponds to methine C-H deformations. 36 The shi of hemoglobin molecules from deoxygenated state to oxygenated state in presence of BPA can be assumed from the increase in 1222 cm À1 peak intensity accompanied by the gradual decrease in 1209 cm À1 from the Fig. 3.…”
Section: Resultsmentioning
confidence: 99%